Major Vault Protein in Macrophages Reprograms Immune Microenvironment and Inhibits Occurrence and Development of Liver Cancer - Zhou, Shimeng; Li, Mengmeng; Wang, Shouyu (Zhongliu fangzhi yanjiu, 2025)
Objective　 To explore the role and molecular mechanism of major vault protein (MVP) in tumorassociated macrophages in the occurrence and development of liver cancer. Methods　The expression of MVP in macrophages was analyzed by bioinformatics method and multi-fluorescent immunohistochemical staining. Mice with MVP deficiency in macrophages were constructed by Cre/LoxP recombinant enzyme system. The proliferation and migration abilities of tumor cells were detected by cloning formation and Transwell migration assays. The effect of MVP in macrophages on tumorigenesis and development was investigated by mouse primary liver cancer model and subcutaneous tumor transplantation model. The effect of MVP on the tumor microenvironment was investigated by multi-fluorescent immunohistochemical staining. The effect of MVP on CD8+ T cells was detected by cell co-culture, flow cytometry, qPCR, and ELISA. Results　The high expression of MVP in tumor-associated macrophages. The downregulation of the expression of MVP in tumor-associated macrophages compared with para-carcinoma tissues. MVP deficiency in macrophages promoted the proliferation and migration of tumor cells (P<0.05), promoted the development of tumor in vivo (P<0.05), formed an immunosuppressive microenvironment and weakened CD8+ T cellmediated anti-tumor immunity (P<0.05). Conclusion　MVP deficiency in macrophages can promote the occurrence and development of liver cancer by suppressing the function of CD8+ T cells.